PENGARUH PEMBELAJARAN MODEL MATH-TALK LEARNING COMMUNITY DAN MODEL DISCOVERY LEARNING TERHADAP PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS DENGAN MEMPERHATIKAN TINGKAT SELF-EFFICACY SISWA - Vara Nina Yulian, - (2023)
This study aims to analyse and describe the effect of learning with the MTLC model and DL models on the acquisition and improvement of students' mathematical communication ability with student's self-efficacy, as well as obtaining a conjecture that relates students' self-efficacy with mathematical communication ability in solving patterns, sequences, and number series problems. The method in this research is mixed method with explanatory sequential design. In the quantitative stage used descriptive and quasi-experimental research with non-equivalent comparison group design and 3 x 2 factorial design. In the qualitative stage used case study with perspective grounded theory systematic procedure. The sample in this study was class VIII students at one of the public junior high schools in the city of Bandung, 66 students. The results showed that: (i) learning the MTLC model had a higher effect on the acquisition and improvement of mathematical communication ability compared to the DL model, (ii) there was no interaction effect between learning and self-efficacy on the acquisition and improvement of mathematical communication ability, (iii) the improvement of students' mathematical communication ability with high self-efficacy is higher than the score of mathematical communication ability with moderate or low self-efficacy, (iv) students who have a high or moderate self-efficacy, achieving all indicators of mathematical communication ability, (v) students who have a low self-efficacy, mathematical communication ability possessed only up to the indicators conceptual models, argumentation, representation, and connecting concepts.